Influence of an inspiratory muscle fatigue protocol on healthy youths on respiratory muscle strength and heart rate variability. A randomized controlled trial - Ladriñán-Maestro, Arturo; Sánchez-Infante, Jorge; Martín-Vera, Daniel; Sánchez-Sierra, Alberto (Frontiers in Physiology, 2024)
Introduction: Inspiratory muscle fatigue has been shown to have effects on the autonomic nervous system and physical condition. This study aimed to evaluate the influence of an inspiratory muscle fatigue protocol on respiratory muscle strength and heart rate variability in healthy youths. Materials and Methods: A randomized controlled clinical trial, employing double-blinding, was conducted with twenty-seven participants aged 18–45 years, non-smokers and engaged in sports activity at least three times a week for a minimum of 1 year. Participants were randomly assigned to three groups: Inspiratory Muscle Fatigue group, Activation group, and Control group. Measurements of heart rate variability, diaphragmatic ultrasound, and maximum inspiratory pressure were taken at two stages: before the intervention and immediately after treatment. Results: In our results with respect to baseline to post-treatment, the inspiratory muscle fatigue group showed lower values in the Sniff contraction velocity variable (10.96 cm/s ± 1.99–8.34 cm/s ± 1.23; p < 0.01) and higher values in the activation group (10.59 cm/s ± 0.89–12.66 cm/s ± 1.15; p < 0.01) with respect to the control group (10.27 cm/s ± 1.48–9.97 cm/s ± 1.42). On the other hand, the inspiratory muscle fatigue group showed higher values in the Low frequency variable (49.37 n.u. ± 13.91 to 69.48 n.u. ± 8.22; p < 0.01) and lower values in the activation group (57.92 n.u. ± 8.37 to 41.59 n.u. ± 11.21; p < 0.01) with respect to the control group (50.83 n.u. ± 17.30 to 52.10 n.u. ± 20.64). Additionally, significant correlations were found between respiratory variables and heart rate variability variables. Conclusion: Acute fatigue of the inspiratory musculature appears to negatively impact heart rate variability and inspiratory muscle strength in healthy youths. Clinical Trial Registration:https://clinicaltrials.gov/study/NCT06278714; Identifier: NCT06278714.